Evaluation of cardiac autonomic dysfunction using electrocardiography in type 2 diabetes mellitus patients: a case-control study - T., Azhar Thouseef Baig; Mahishale, Gajendra S.; Vinay Kumar, M. (International Journal of Research in Medical Sciences, 2025)
Background: Type 2 diabetes mellitus (T2DM) is associated with a high risk of cardiovascular complications, including cardiac autonomic neuropathy (CAN), which significantly increases morbidity and mortality. Electrocardiography (ECG) offers a non-invasive method to detect cardiac dysautonomia early. This study aimed to evaluate ECG changes in T2DM patients and correlate them with cardiac autonomic dysfunction. Methods: A cross-sectional observational study was conducted on 50 T2DM patients and 50 age- and gender-matched healthy controls. Standard 12-lead ECG was performed to assess heart rate, RR interval, PR interval, QRS duration, QRS axis, and QTc interval. Cardiac autonomic function was evaluated using heart rate variability (HRV) parameters and clinical autonomic tests. Statistical analysis was performed to compare ECG parameters and prevalence of ischemic and conduction abnormalities between groups. Results: T2DM patients exhibited significantly higher mean heart rates (86.9±10.81 versus 78.78±11.26 beats/minute; p=0.001), prolonged PR interval (162.40±31.72 versus 138.20±16.98 msec; p=0.001), increased QRS duration (70.98±12.72 versus 65±8.63 msec; p=0.007), and prolonged QTc interval (410.63±43.80 versus 329.20±29.74 msec; p=0.001) compared to controls. Additionally, ischemia (20% versus 4%; p=0.01), infarction (22% versus 6%; p=0.02), and conduction blocks (14% versus 2%; p=0.02) were significantly more prevalent in T2DM patients. HRV analysis indicated reduced autonomic function in the diabetic group. Conclusions: T2DM is associated with significant ECG abnormalities reflecting cardiac dysautonomia and increased cardiovascular risk. ECG can serve as a valuable tool for early detection of CAN in diabetic patients, enabling timely intervention to reduce adverse outcomes.